2019
DOI: 10.1111/cen.13953
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise and Prader‐Willi syndrome: A systematic review

Abstract: Summary Objective The aim of this systematic review was to summarize evidence on the acute responses of individuals with Prader‐Willi syndrome (PWS) to physical exercise, and on the effectiveness of long‐term exercise interventions to improve the clinical manifestations of this syndrome. Design/methods Relevant articles were identified in the electronic databases PubMed, Medline, CINAHL and SPORTDiscus (from inception to December 2018). Twenty‐two studies including a total of 356 patients with PWS met all incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…All the studies investigating the acute and long‐term responses to increased physical activity in individuals with PWS have recently been systematically reviewed; please refer to Morales et al for a detailed description of these studies . Compared with controls with normal weight and obesity, children with PWS exhibited a similar hormonal response to a single session of resistance training but no significant changes in epinephrine and norepinephrine after an endurance training session.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies investigating the acute and long‐term responses to increased physical activity in individuals with PWS have recently been systematically reviewed; please refer to Morales et al for a detailed description of these studies . Compared with controls with normal weight and obesity, children with PWS exhibited a similar hormonal response to a single session of resistance training but no significant changes in epinephrine and norepinephrine after an endurance training session.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to restricting caloric intake, daily exercise is necessary to prevent morbid obesity and its complications in PWS (Cassidy & Driscoll, ; Grolla, Andrighetto, Parmigiano, et al, ; Morales et al, ). Programs for physical activity in PWS individuals usually consist mainly of aerobic exercise (Hirsch et al, ; Morales et al, ; Silverthorn & Hornak, ). Resistance exercises for strength training, however, may be particularly important to increase muscle mass in this population with hypotonia and abnormal body composition (Eiholzer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…spontaneous PA performed independently of exercise training) in children with PWS but this has not been assessed in adults. As recently reviewed, different types of exercise programmes have been conducted in adults with PWS (Morales et al, ) and most programmes were supervised and performed in a residential or community setting (Cimolin et al, ; Grolla et al, ; Kaufman, Overton, Leggott, & Clericuzio, ; Shields, Bennell, Radcliffe, & Taylor, ; Silverthorne & Hornak, ). This literature review found that residential programmes that are organized several times per year and include dietary restriction, a high daily amount of supervised PA and a structured environment substantially reduced body mass over a long‐term period (Cimolin et al, ; Grolla et al, ; Kaufman et al, ).…”
Section: Introductionmentioning
confidence: 99%